2002
DOI: 10.1007/s00221-002-1020-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pallidal deep brain stimulation and levodopa treatment on reaction-time performance in Parkinson’s disease

Abstract: Basal ganglia-thalamocortical circuits play an important role in movement preparation and execution. Tracer, single-cell, and lesion studies in monkeys suggest the existence of topologically segregated motor and nonmotor basal ganglia cortical circuits. In this study we used deep brain stimulation (DBS) of the posteroventrolateral globus pallidus internus (GPi) in patients with Parkinson's disease to elucidate the function of the GPi in human sensorimotor behavior. This question was investigated by comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…Previous studies of pointing by sitting PD subjects with similar disease severity have reported significantly more slowing and significantly larger than normal constant and variable pointing errors (Flowers 1975; Poizner et al 1998; Adamovich et al 2001b; Schubert et al 2002; Maschke et al 2003; Keijsers et al 2005). Decrements in performance of PD subjects with eyes closed have been ascribed to impairment of proprioceptive integration for precise, voluntary movements (Adamovich et al 2001b; Maschke et al 2003).…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies of pointing by sitting PD subjects with similar disease severity have reported significantly more slowing and significantly larger than normal constant and variable pointing errors (Flowers 1975; Poizner et al 1998; Adamovich et al 2001b; Schubert et al 2002; Maschke et al 2003; Keijsers et al 2005). Decrements in performance of PD subjects with eyes closed have been ascribed to impairment of proprioceptive integration for precise, voluntary movements (Adamovich et al 2001b; Maschke et al 2003).…”
Section: Discussionmentioning
confidence: 76%
“…However, those few studies directly assessing bradykinesia in reaction time/movement velocity studies have consistently demonstrated improvements in bradykinesia. 914 Reports of motor cortex 15, 16 and GPe stimulation 1720 also describe improvement in clinical measures of bradykinesia. Again, the evidence is limited, but what evidence is available has been positive.…”
Section: Discussionmentioning
confidence: 99%
“…However, highly discordant results have been reported [2] and this symptom is still poorly understood [3]. As a consequence, movement initiation disorders are not easily alleviated by standard therapies [4][5][6]. Even worse, they can be aggravated by the treatments, for example worsened akinesia [7] or induced impulsivity [8][9][10].…”
Section: Introductionmentioning
confidence: 99%